Analogs of Ridge Skin and Papillary Patterns in the Nature and the Significance of Their Study for Forensic Science and Forensic Examination - Sh. N. Khaziev (Теория и практика судебной экспертизы, 2022)
Patterns similar to the papillary patterns of human fingers, palms, and soles can be found in living and inanimate nature. Studying such patterns and the structure of the ridged skin of humans and primates in comparison with similar formations on other objects is necessary for forensic science, forensic traceology, fingerprinting, and biometric identification. The article analyzes the history of the study of the ridged skin of humans, primates, and other animals by forensic scientists, zoologists, anthropologists, and representatives of other sciences.The author proposes systemizing and classifying the information about the analogs of papillary patterns and ridged skin on such grounds as the genus and type of carrier objects, relief structure, degree of comparability with the papillary pattern of human hands and soles.The article presents the most indicative varieties of analogs of papillary patterns in mammals, birds, fish, insects, corals, plants, and fungi. The author has studied and systemized structural features of the striped pattern of the skin of tigers and zebras, crests and stripes in corals, stripes and ridged patterns in fish. The data obtained on ridge formations, which are similar in structure and shape to the papillary patterns of human fingers and palms, will help to avoid expert errors during fingerprinting examination or erroneous placement of images of such formations in forensic databases.Knowledge of the structural features and properties of striped patterns of skins of specially protected wild animals, as well as the crest surface of paleontological museum objects, should be used for their identification by photo and video images in cases of embezzlement, smuggling, illegal hunting, and illegal trafficking.